Phylogenomic, Morphological, and Phylogenetic Evidence Reveals Five New Species and Two New Host Records of Nectriaceae (Hypocreales) from China - Qi Fan; Pingping Su; Jiachen Xiao; Fangwei Lou; Xiaoyuan Huang; Zhuliang Yang; Baozheng Chen; Peihong Shen; Yuanbing Wang (Biology, 2025)
Fusarioid fungi, members of the Nectriaceae within the Hypocreales (Ascomycota), exhibit diverse ecological roles and possess complex phylogenetic relationships, including endophytic, saprophytic, and pathogenic lifestyles. Among them, the genera Fusarium and Neocosmospora are particularly significant in agriculture and medicine. However, the boundaries between their species remain taxonomically contentious. In this study, 22 representative isolates from plant, fungal, and insect hosts were subjected to a polyphasic taxonomic approach that integrated morphological characterization, multilocus phylogenetic analyses, and phylogenomic analysis based on 4,941 single-copy orthologous genes. Consequently, five new species (F. dracaenophilum, F. puerense, F. wenshanense, N. alboflava, and N. fungicola) were described, and F. qiannanense and N. solani were recorded from new host species. The resulting phylogenomic tree topology was highly congruent with the multilocus phylogeny, providing robust support for the taxonomic distinction between Fusarium and Neocosmospora. This study provides new insights into the taxonomy of fusarioid fungi and has important implications for plant disease management, biodiversity conservation, and the study of fungal evolution.